The Carceral Continuum and the Penitentiary System in Ukraine - Romanov, Mykhailo (Problems of legality, 2025)
The penitentiary system is an integral part of the carceral continuum. It is one of its ultimate boundaries. It is there that the main tendencies in the approach to the education of a disciplined individual can be traced. Obviously that this approach has not had much success in Ukraine, as the achievements over thirty years of reforms have been very modest. The article attempts to examine the problems, existing standards and the situation in Ukrainian prisons. To critically rethink the recommendations and identify the reasons why they are not being implemented and may not be implemented. If they cannot be implemented, what prevents this and what is the possible way forward or out of the current situation. Methodology - this short study is based on an examination of the problems of the structural penitentiary system of Ukraine and the proposed solutions to them. The official view on these problems by the Government of Ukraine and the recommendations and reports of international organisations and the European Court of Human Rights have been taken as a basis. The study concluded that Ukraine does not have an institutionalised carceral system and that approaches applied to such systems in other countries will not have a positive effect. Successful reform of the penitentiary system and its humanisation require a comprehensive social, political and legal effort, which must take place against a background of rethinking the place and role of prison in dealing with those who have committed crime.